Deterrence Effects: The Role of Authoritarian Leadership in Controlling Employee Workplace Deviance. (May 2020) - Zheng, Yuyan; Huang, Xu; Graham, Les; Redman, Tom; Hu, Saiquan
ABSTRACT: Drawing upon two independent samples from mainland China, we propose and investigate the deterrence function of leadership behavior focused on control. We suggest that controlling leadership, specifically, authoritarian leadership, deters employees' deviance under certain conditions. That is, authoritarian leadership thwarts employees' interpersonal deviance behavior when leaders send clear signals of potential punishments of non-compliance by showing low leader benevolence, and when employees are highly dependent on the leaders for important work resources. Results from two independent studies largely support our key propositions. Overall, these results add to the range of possible impacts that a leader can play in decreasing employee deviance. Theoretical implications and directions for follow-up research are discussed.